Ice anaesthesia in procedural dermatology. (26th April 2013) - Dixit, Shreya; Lowe, Patricia; Fischer, Gayle; Lim, Adrian
Abstract: This article presents findings from a survey of Australian dermatologists who were questioned about their preferred pain control methods when carrying out injectable procedures. We also present, what is to the best of our knowledge, the first proof‐of‐concept experiment exploring the relationship between ice‐to‐skin contact time and skin surface temperature, using both ice wrapped in latex and ice wrapped in aluminium foil. Of 79 dermatologists 32 responded to the survey (41% response rate): 31 (97%) injected botulinum toxin type A (BTA) for dynamic lines, 26 (81%) injected BTA for hyperhidrosis, and 24 (75%) injected skin fillers. Ice anaesthesia was the most common method of pain control (75%) followed by use of topical anaesthesia (50%) such as EMLA, compound agents and lignocaine 4%. Ice wrapped in latex or latex‐like material was the most common ice packaging used by those surveyed and the median ice‐to‐skin contact time was 10 s. The ice experiment results indicated that ice wrapped with aluminium foil was equivalent to ice wrapped in latex for short contact times (< 20 s), but more effective at reducing skin temperature with longer contact times (> 20 s). These findings will be of relevance to cosmetic and paediatric dermatologists or any area of procedural medicine where effective non‐injectable pain control is required.